RECONTRUCTION GUARANTEE CONFISCATION AS AN ALTERNATIVE APPROACH TO MAXIMIZE THE STATE-LOSSES RECOVERY - QOHAR AF, ABDUL (Jurnal Independent, 2022)
Abstract In addition, the argument for violating human rights is also inappropriate to reject the idea of guarantee confiscation. The limitation of a right to law enforcement is justified by the 1945 Constitution and control of the confiscated objects is still given to the suspect. Speaking of option of legal efforts that can be accessed by the suspect, pretrial is one of the option available. Pretrial can assess the validity of the confiscation by looking at the letter of determination from the local district court and the urgency of carrying out the action. The proposed change in procedural law in handling corruption cases is actually in line with a restorative approach. This has also been pushed by the government, at least through President Joko Widodo's statement regarding the urgency of recovering state financial losses in handling corruption cases. However, changes in legislation of course do not only rely on the executive, but also on the legislative side. Up to now, th legislative products that support the agenda of eradicating corruption have not been prioritized by legislators, such as Bill on Asset Confiscation, Bill on Limitation of Currency Transactions, as well as the Revision of the Anti Corruption Law. Therefore, this study must also be followed up by the awareness from the government and the parliament about the current stagnation of law enforcement to eradicate corruption.